2017
DOI: 10.1002/ddr.21412
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 Prevents the Interleukin‐1 Beta Induced Inflammatory Response via Inhibition of MAPK Signaling Pathways in Rat Articular Chondrocytes

Abstract: Preclinical Research Osteoarthritis (OA) is a widely prevalent degenerative joint disease that severely impairs the health of the elderly population resulting in a heavy economic burden worldwide. Coenzyme Q10 (CoQ10) has shown anti-inflammatory effects in some diseases. The present study aimed to investigate if CoQ10 would suppress catabolic responses of interleukin (IL)-1β-induced chondrocytes. Rat chondrocytes were cultured and pretreated with CoQ10, and then stimulated with or without IL-1β (10 ng/ml). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Cell Viability Assay. Cell viability was evaluated using a WST-1 assay [27]. In brief, BMSCs were seeded into a 96-well plate at a density of 1 × 10 4 /well.…”
Section: Differentiation Of the Bmscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell Viability Assay. Cell viability was evaluated using a WST-1 assay [27]. In brief, BMSCs were seeded into a 96-well plate at a density of 1 × 10 4 /well.…”
Section: Differentiation Of the Bmscsmentioning
confidence: 99%
“…Western Blotting Analysis. Western blotting experiments were performed following standard methods [27]. In brief, the proteins were loaded onto 10% SDS-PAGE and electrotransferred onto polyvinylidene difluoride membranes (Millipore, USA).…”
mentioning
confidence: 99%
“…Previous studies showed that inhibition of the production of iNOS, COX‐2, and MMPs acted through the MAPK signaling pathway (Chen et al, ; Ma et al, ). Moreover, activating MAPKs has been associated with the progress of OA (Feng et al, ; Li et al, ). IL‐1β‐induced chondrocytes can increase the phosphorylation levels of p38, ERK, and JNK.…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability was determined by WST‐1 assay according to the manufacturer's instructions (Li et al, ). Briefly, chondrocytes were cultured in a 96‐well plates (1 × 10 4 /well) for 24 hr.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation